THE EFFECTS OF VARIATION OF CATALYST CONCENTRATION ON BIODIESEL PRODUCTION - Nahadi, Janet John; Atadashi, Musa Idris (International Journal of Research -GRANTHAALAYAH, 2018)
Biodiesel is defined as mono-alkyl esters of long chain fatty acids derived from vegetable oils or animal fats, which conform to ASTM D6751 specifications for use in diesel engines. Fuel-grade biodiesel must be produced to strict industry specifications in order to ensure proper performance. Biodiesel contains no petroleum, but it can be blended at any level with petroleum diesel to create a biodiesel blend. From the production and characterization of biodiesel via the alkaline transesterification of coconut oil using different concentrations homogeneous catalyst (sodium hydroxide), oil to methanol molar ratio of 1:6, reaction temperature of 550C and reaction time of 60 min. Biodiesel can serve as a potential feedstock for the production of biodiesel owing to its high conversion rate and relatively low FFA content. At a catalyst concentration of 1%w/w oil NaOH catalyst, optimum yield of up to 96% was achieved. It is interesting to note that the viscosity of the biodiesel obtained falls within the limit as specified by ASTM D445 (2003). A flash point of 154.2 was obtained for the coconut biodiesel. This shows that the biodiesel is safe for handling as the flash point exceeds the minimum stipulated by the ASTM (93min). The transformation of the triglycerides present in most oils into methyl ester was confirmed by FT-IR studied. Further investigation regarding the profile of the acid methyl esters present in the oil was confirmed using GC-MS analysis.